Formulasi Lingkaran Mandala Kebijakan Luar Negeri Indonesia Pasca Jokowi: FPA - Fathun, Laode; Zahra Nathania, Vania; Pringgo Sejati, Satryo; Din Aulia, Jamal; Nurlaela, Della (Andalas Institute of International Studies, 2025)
This paper aims to describe the formulation of the Mandala of Indonesia’s foreign policy in the post Jokowi era. The main focus of this study is the recognition that both domestic and international political situations are constantly evolving. Moreover, differences in leadership styles lead to variations in the tactics and strategies adopted. This study employs secondary data as the basis of analysis through a literature review. The theoretical framework applied is the Mandala model of foreign policy. The findings indicate that the formulation of Indonesia’s foreign policy is influenced by domestic and international factors as well as leadership style and experience. In the post Jokowi era President Prabowo whose approach differs from that of his predecessors such as Susilo Bambang Yudhoyono and Joko Widodo has adopted distinct strategies and tactics. Prabowo is characterized by strategic tactical and hierarchical thinking. This style reshapes Indonesia’s Mandala model compared to previous administrations. Consequently internal and external challenges will require Prabowo to be both a smart leader in diplomacy and a smart leader in decision making. Given the ever changing dynamics innovation and adaptability will be essential.